One-pot green route synthesis of silver nanoparticles from jack fruit seeds and their antibacterial activities with escherichia coli and salmonella bacteria. (July 2019) - Chandhru, M.; Logesh, R.; Rani, S. Kutti; Ahmed, Neesar; Vasimalai, N.
Abstract: The present work describes an economical viable and environmental friendly synthesis of silver nanoparticles from jack fruit seeds extract (JFS-AgNPs) at room temperature and their antibacterial studies. The synthesized JFS-AgNPs was characterized by UV–vis spectral, X-ray diffraction pattern (XRD), Fourier transform infrared spectroscopy (FT-IR), Dynamic light scattering (DLS) and High resolution transmission electron microscopy (HR-TEM) techniques. The JFS-AgNPs are stable for four months and the average diameter of the particles was calculated to be 22.12 ± 1.05 nm by HR-TEM. Then, JFS-AgNPs was successfully applied for the antibacterial studies with of escherichia Coli ( E.coli ) and salmonella ( Salmonella Enterica Typhimurium ) bacteria. JFS-AgNPs showed antibacterial activities against E. coli and Salmonella bacteria. Further, we have compared the antibacterial efficiency of our JFS-AgNPs with ampicillin antibiotic drug. It is anticipated that JFS-AgNPs can provide the future opportunity in nanomedicine and material science. Graphical abstract: Image 1 Highlights: Economical viable and Green synthesis of Jack fruit seeds based silver nanoparticles. The synthesized JFS-AgNPs are stable for four months. The JFS-AgNPs showed antibacterial activity against E. coli and Salmonella bacteria. Minimum inhibitory concentration (MIC) and minimum bacterial concentration (MBC) studies were performed. Ampicillin drug was used as a positive control.